2008
DOI: 10.1177/0898264308324626
|View full text |Cite
|
Sign up to set email alerts
|

Differential Associations of Social Support and Social Connectedness With Structural Features of Social Networks and the Health Status of Older Adults

Abstract: Perceived social connectedness may be relatively more important to the health and well-being of older adults than the perceived availability of social support. Efforts to enhance older adults' social relationships can be focused on developing friends and companions, allowing them to feel socially engaged in society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
210
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 248 publications
(237 citation statements)
references
References 32 publications
17
210
0
10
Order By: Relevance
“…On the most general level, Ashida and Heaney (2008) corroborated previous studies, with their results indicating that having frequent contacts with more network members is positively associated with higher social support, while Ajrouch et al (2001) noted that the ego's age 1 has a negative effect on the frequency of contact with network members. However, the magnitude of this effect can vary according to the relationship between the ego and the alter, although older adults have fewer contacts with friends, they remain in stable contacts with family members (Shaw et al, 2007).…”
Section: The Social Support Network Of Older Adultssupporting
confidence: 84%
“…On the most general level, Ashida and Heaney (2008) corroborated previous studies, with their results indicating that having frequent contacts with more network members is positively associated with higher social support, while Ajrouch et al (2001) noted that the ego's age 1 has a negative effect on the frequency of contact with network members. However, the magnitude of this effect can vary according to the relationship between the ego and the alter, although older adults have fewer contacts with friends, they remain in stable contacts with family members (Shaw et al, 2007).…”
Section: The Social Support Network Of Older Adultssupporting
confidence: 84%
“…This is consistent with the literature that shows rather low levels of communication about chronic disease FHH among the public (Yoon et al 2004) and highlights our missed opportunities in chronic disease prevention especially among those at increased risk due to family history. The average size of the currently living network and levels of support exchange reported by the participants in this study were similar (Antonucci and Akiyama 1987) or slightly smaller than previously reported (Ashida and Heaney 2008) and is likely due to the current study's focus on the FHH communication network rather than an overall social support network. Disseminating FHH information to biological children is especially important because these adult children can later inform the younger family members when they reach an appropriate age.…”
Section: Discussionsupporting
confidence: 64%
“…This single-item question was adapted by the investigators because of increasing evidence that the presence of a confidant is strongly associated with both dimensions of instrumental and emotional support; the availability of roles and attachment (ie, marital status, number of living children and siblings) is not. 37 Research also shows that a person's appraisal of social support may be even more important than actual interpersonal contacts 38 ; that perceived availability of social support can be a source of general positive affect, enhanced self-esteem, and feelings of belonging and security. 39 Furthermore, the belief that there are people available to care about an individual and who would try to help if help were needed maybe the key factor in the efficacy of social support in promoting physical and psychological health.…”
Section: Control Attitude Scalementioning
confidence: 99%